Bentuk Wacana Fatis dalam Interaksi Sosial Masyarakat Jawa (Forms of Phatic Discourse in the Javanese Social Interaction) - Rangga Asmara; I Dewa Putu Wijana; Sulistyowati Sulistyowati (Jurusan Tadris Bahasa Indonesia, 2023)
This research aims to describe the formal forms or manifestations of phatic discourse within the conversational discourse structure among the Javanese community. The data in this research are phatic discourses as units filling conversational/interactive discourse. Data collection was centered in Magelang. Data collection was carried out through non-participant observation techniques involving 22 respondents. During the data collection process, the researcher also conducted recording, notation, and translation. The analytical methods used in this research are referential equivalence, pragmatic equivalence, and distributional methods. Based on the research, in terms of form, phatic discourse is constructed with sentence-forming elements of news, questions, and commands. This proves that phatic discourse can be used in all modes of communication, whether declarative, interrogative, or imperative. However, pure phatic discourse with sentence-forming elements of commands was not found in its usage. In Javanese social interaction, phatic discourse is present and used as words that do not convey meaning but serve a social function.Penelitian ini bertujuan mendeskripsikan bentuk formal atau wujud wacana fatis dalam struktur wacana percakapan di kalangan masyarakat Jawa. Data dalam penelitian ini ialah wacana fatis sebagai satuan pengisi wacana percakapan/interaktif. Latar pengambilan data dipusatkan di Magelang. Pengumpulan data dilakukan dengan teknik observasi nonpartisipan yang melibatkan 22 responden. Selama pengumpulan data berlangsung, peneliti juga juga melakukan perekaman, pencatatan, dan pentranslasian. Metode analisis yang dipergunakan dalam penelitian ini adalahÂ metode padan referensial, padan pragmatis, metode agih. Berdasakan penelitian, dari segi bentuk, wacana fatis dikonstruksi dengan unsur pembentuk kalimat berita, tanya, dan suruh. Hal ini membuktikan wacana fatis dapat digunakan pada semua modus komunikasi, baik deklaratif, interogatif, dan imperatif. Namun demikian, wacana fatis dengan unsur pembentuk kalimat suruh murni tidak ditemukan penggunannya. Dalam interaksi sosial masyarakat Jawa, wacana fatis hadir dan digunakan sebagai kata-kata yang tidak membawa arti, melainkan untuk memenuhi suatu fungsi sosial.